Kebijakan Pemerintah dalam Penanganan Pencemaran Minyak di Perairan Laut - Intan Fandini; Suwari Akhmaddhian (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
Marine pollution is the entry/inclusion of living things, energy substances and or other components into the marine environment by human activities so that the quality decreases to a certain level which causes the marine environment to no longer comply with quality standards and/or functions. One of the cases related to environmental pollution that caused damage to the marine environment was the Oil Spill in the Back Sea Waters of Padang, Batam, Riau Islands Province. The purpose of this paper is to find out how the policy in the petroleum sector in Indonesia is, how is the regulation of Indonesian national law to prevent, reduce and control the problem of marine pollution by oil, how is the impact of oil spills in sea waters from oil and gas industry activities on the environment. The method used in this research is the normative juridical method. Using qualitative analysis with the resulting data in the form of secondary data obtained from previous research, laws and regulations and other sources. The result of this research is that the policy of the petroleum sector in Indonesia to achieve energy security is pursued by applying the concept of State Controlling Rights (HMN). The philosophy of "control by the state" is the creation of national security in the energy sector in the Unitary State of the Republic of Indonesia with the main target of providing and distributing energy throughout its territory. Regulation of national law through Government Regulation concerning Control of Marine Pollution and/or Destruction, which was followed up with the issuance of Presidential Regulation concerning the Handling of Marine Debris. The impact of waste in the form of oil spills specifically shows an important negative effect on the coastal and marine environment, especially through direct contact with aquatic organisms, direct impacts on fisheries activities including marine tourism and indirect impacts through disturbances to the environment.